Comparative trial of two non-sedative H1 antihistamines, terfenadine and astemizole, for hay fever. Issue 9 (September 1984) - Howarth, P H; Holgate, S T
Abstract : Ninety patients participated in a randomised, double blind, placebo controlled comparison of terfenadine with astemizole in the treatment of hay fever. They entered the trial as a cohort before the grass pollen season and recorded daily their symptoms of itching eyes, sneezing, running nose, and blocked nose on visual analogue scales in diary cards. Over the eight weeks of the trial astemizole was significantly better than either terfenadine or placebo in alleviating itching eyes, sneezing, and running nose (p less than 0.0001) but no better than placebo for the treatment of blocked nose. The placebo was significantly better than terfenadine for the treatment of running nose and blocked nose (p less than 0.002). Neither of these H1 antihistamine drugs was associated with sedative adverse effects despite significantly inhibiting histamine induced skin weal responses. These results suggest that astemizole is a satisfactory non-sedative H1 antihistamine for maintenance treatment of hay fever. Terfenadine is ineffective by comparison.